Mental Health and Psychological Well-Being among Prisoners: An Empirical Perspective - Dr. Asma Batcha; Dr. Syed Umarhathab (The Bioscan, 2026)
Mental health and psychological well-being are critical yet often overlooked components of prisoner welfare, particularly among under-trial inmates who face prolonged uncertainty, social isolation, and systemic delays. The present study examined the levels of mental health and psychological well-being among 147 under-trial prisoners, assessed the relationship between these variables, and explored differences across selected demographic and criminological characteristics. Using standardized psychological assessment tools, the results indicated that inmates displayed below-average mental health, marked by symptoms of anxiety, depression, stress, and social dysfunction, while psychological well- being was found to be moderate. Statistical analysis revealed a strong, significant negative correlation between mental health problems and psychological well-being, suggesting that increased psychological distress corresponded with reduced well-being. Significant differences were also observed across variables such as age, education, marital status, duration of imprisonment, and nature of crime. The findings underscore the necessity for structured psychological assessment, therapeutic interventions, and rehabilitative prison policies to promote inmate well-being. The study concludes with recommendations aimed at transforming prison settings into mental health–supportive, rehabilitative environments aligned with national and international correctional standards.